Targeted Antimicrobial Therapy Against Streptococcus mutans Establishes Protective Non-cariogenic Oral Biofilms and Reduces Subsequent Infection - Li, Li-na (Nature Publishing Group, 2010)
AIM: Dental biofilms are complex communities composed largely of harmless bacteria. Certain pathogenic species including Streptococcus mutans (S. mutans) can become predominant when host factors such as dietary sucrose intake imbalance the biofilm ecology. Current approaches to control S. mutans infection are not pathogen-specific and eliminate the entire oral community along with any protective benefits provided. Here, we tested the hypothesis that removal of S. mutans from the oral community through targeted antimicrobial therapy achieves protection against subsequent S. mutans colonization. METHODOLOGY: Controlled amounts of S. mutans were mixed with S. mutans-free saliva, grown into biofilms and visualized by antibody staining and cfu quantization. Two specifically-targeted antimicrobial peptides (STAMPs) against S. mutans were tested for their ability to reduce S. mutans biofilm incorporation upon treatment of the inocula. The resulting biofilms were also evaluated for their ability to resist subsequent exogenous S. mutans colonization. RESULTS: S. mutans colonization was considerably reduced (9 ± 0.4 fold reduction, P=0.01) when the surface was preoccupied with saliva-derived biofilms. Furthermore, treatment with S. mutans-specific STAMPs yielded S. mutans-deficient biofilms with significant protection against further S. mutans colonization (5 minutes treatment: 38 ± 13 fold reduction P=0.01; 16 hours treatment: 96 ± 28 fold reduction P=0.07). CONCLUSION: S. mutans infection is reduced by the presence of existing biofilms. Thus maintaining a healthy or “normal” biofilm through targeted antimicrobial therapy (such as the STAMPs) could represent an effective strategy for the treatment and prevention of S. mutans colonization in the oral cavity and caries progression.